2010
DOI: 10.1364/oe.18.000893
|View full text |Cite
|
Sign up to set email alerts
|

Spectral beam combining of a 980 nm tapered diode laser bar

Abstract: Abstract:We demonstrate spectral beam combining of a 980 nm tapered diode laser bar. The combined beam from 12 tapered emitters on the bar yielded an output power of 9.3 W at 30 A of operating current. An M 2 value of 5.3 has been achieved along the slow axis. This value is close to that of a free running single tapered emitter on the bar at the same current level. The overall spectral beam combining efficiency was measured to be 63%. ©2010 Optical Society of America

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…The tapered resonant cavity has been widely adopted in near-infrared diodes [5][6][7][8] and midinfrared QCLs [9][10][11][12][13]. The introduction of the tapered region may affect the propagation of the fundamental mode of the light field, threshold current and output power of laser devices.…”
Section: Basic Properties Of a Tapered Thz Qclmentioning
confidence: 99%
“…The tapered resonant cavity has been widely adopted in near-infrared diodes [5][6][7][8] and midinfrared QCLs [9][10][11][12][13]. The introduction of the tapered region may affect the propagation of the fundamental mode of the light field, threshold current and output power of laser devices.…”
Section: Basic Properties Of a Tapered Thz Qclmentioning
confidence: 99%
“…simultaneous SHG and SFG Spectral beam combination of fiber lasers have been demonstrated with up to 5 lasers [97] and with diode lasers significantly more lasers have been combined [100]- [104]. If the wavelengths of these combined lasers are chosen properly, it is possible to obtain efficient frequency conversion of several lasers simultaneously and generation of light at a single wavelength can be achieved while operating the nonlinear crystal at a constant temperature.…”
Section: Spectral Beam Combination Of Three Lasers Andmentioning
confidence: 99%
“…In this context combining of a 100 emitter array reaching 35 W in pulsed mode at 915 nm with a beam quality of 1.4 was reported [20]. Vijayakumar et al demonstrated the first ever combining of a tapered diode laser bar reaching 9.3 W with a combining efficiency of 63% [21]. However, diode laser arrays have the disadvantage of mounting induced smiles, leading to a degradation of the beam quality even when the array consists of individual near diffraction limited emitters [20].…”
Section: Introductionmentioning
confidence: 96%
“…This also proofs the reliability of such gratings within a large power range. The increase in combining efficiency compared to the combining of diode laser arrays [21] might result from an increased flexibility in terms of optical alignments and adjustments of laser parameters.…”
Section: Introductionmentioning
confidence: 99%